Angels on Earth [large type] : inspiring stories of fate, friendship, and the power of connections - Schroff, Laura; Tresniowski, Alex (Wheeler Publishing, 2017)
From the international bestselling authors of A Invisible Thread comes a heartwarming book about the incredible impact that acts of kindness from strangers can have on the world around us. Angels on Earth will introduce a series of remarkable people whose invisible thread stories will move, surprise, and inspire.